Peningkatan Literasi Bahasa dan Budaya Indonesia berbasis Cerita Rakyat bagi Anak Migran di Segambut, Kuala Lumpur, Malaysia - Diana Hardiyanti; Heri Dwi Santoso; Asphaninda Ratu Dewanti; Arviza Puterizahra (PT. Willy Print Art, 2025)
Indonesian migrant children in Malaysia face educational and identity-related challenges because some of them have limited access to formal schooling and grow up in multilingual environments that may reduce their exposure to Indonesian language and culture. This community service program aimed to strengthen Indonesian language and cultural literacy among Indonesian children at the Segambut Learning Center, Kuala Lumpur. The program was conducted through a participatory educational approach involving coordination with learning center administrators, preparation of Indonesian folklore-based learning materials, interactive storytelling, guided reading, role play, traditional songs, and reflective evaluation. The target participants were 45 Indonesian children aged 5 to 11 years. Data were collected through observation, short oral questions, retelling activities, and feedback from the learning center. The results indicate that folklore-based activities created an engaging literacy space, encouraged children to listen, respond, retell stories, and use Indonesian expressions in meaningful contexts. The activities also introduced cultural values through stories such as Maling Kundang, Roro Jonggrang, and Cindelaras. This program shows that culturally responsive storytelling can serve as an accessible strategy to support heritage language maintenance, cultural awareness, and national identity formation among Indonesian migrant children. Continued mentoring and structured reading materials are recommended to sustain the impact of the program.